(3hUjI WHjIs - (3CHh YHO Gddg eMeO Hf eMeO Hf Ydj Hf YHO Gddg GddNej GdTbhQj,J (B749 (3g` s ((3Ydi Hf bGSe Hf Ydi GdHjGVi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf JMbjb Cf SHHg aSGO eHKhK ai GdghGA GdeJfaS ajg ,adPdc CeQ GdCWHGA HEUdGM GdghGA s
(3BNQgG (B:s
(3hef Yf dg TF , Ch CTcGd Ydjg CeQ adjSCd ajg , hjHjf dg Ydi CJe hLgg HaVd Gddg hbhJg , hGdMeO ddg , hSdGe Ydi YHGOg GdPjf GUWai s
(3Vef eLehY , JQJjHgG (B: (3ef U (B26 - (3U(B33s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B285 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B71s
GAL - - (3U (B379 ; GAL - (3GdLRA (B3 - (3U (B1279 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GKGfi (B- (3U (B283 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs